If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3h + 4)(2h + -5) = 0 Reorder the terms: (4 + 3h)(2h + -5) = 0 Reorder the terms: (4 + 3h)(-5 + 2h) = 0 Multiply (4 + 3h) * (-5 + 2h) (4(-5 + 2h) + 3h * (-5 + 2h)) = 0 ((-5 * 4 + 2h * 4) + 3h * (-5 + 2h)) = 0 ((-20 + 8h) + 3h * (-5 + 2h)) = 0 (-20 + 8h + (-5 * 3h + 2h * 3h)) = 0 (-20 + 8h + (-15h + 6h2)) = 0 Combine like terms: 8h + -15h = -7h (-20 + -7h + 6h2) = 0 Solving -20 + -7h + 6h2 = 0 Solving for variable 'h'. Factor a trinomial. (-4 + -3h)(5 + -2h) = 0Subproblem 1
Set the factor '(-4 + -3h)' equal to zero and attempt to solve: Simplifying -4 + -3h = 0 Solving -4 + -3h = 0 Move all terms containing h to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -3h = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -3h = 0 + 4 -3h = 0 + 4 Combine like terms: 0 + 4 = 4 -3h = 4 Divide each side by '-3'. h = -1.333333333 Simplifying h = -1.333333333Subproblem 2
Set the factor '(5 + -2h)' equal to zero and attempt to solve: Simplifying 5 + -2h = 0 Solving 5 + -2h = 0 Move all terms containing h to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2h = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2h = 0 + -5 -2h = 0 + -5 Combine like terms: 0 + -5 = -5 -2h = -5 Divide each side by '-2'. h = 2.5 Simplifying h = 2.5Solution
h = {-1.333333333, 2.5}
| 1/4-x=23 | | 3x(5-2x)=-6x(x+2)+81 | | =-6(h+3)-8(h-7) | | 106=6x+4(-3x+34) | | 1/3x^(2/3) | | 14x+30=12x-58 | | 0=1/3x^2/3 | | 5x+18=34 | | 0=-2(x-1) | | 2y=500-2x | | 2x=500-2y | | 132=-50-7x | | 0=2(x+2) | | 3.2x+2.3=-9.4 | | 9x-7=3x+12 | | abs(6x)-4=0 | | 8x-12=x+10 | | -14=x/2-6 | | x+x+y+y=500 | | 17=2s+1 | | -x+188=-436+15x | | 4hsquared-2h(h-2)= | | 3tg^2(5x)-9=0 | | 10x-15=9x+3 | | =-14g-21+24g+16 | | 3n+10=n-7 | | =7(-2g-3)+8(3g-2) | | -12(-8x-39)=-588 | | 2m-55n7/14m6n3 | | 2.3x*3.2=-9.4 | | -3(y-2y)+4=-3(2y-y)+8+5y | | -5+55=55 |